2016
DOI: 10.1159/000450611
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the <b><i>ydiB</i></b> Gene, Which Encodes Quinate/Shikimate Dehydrogenase, in the Production of Quinic, Dehydroshikimic and Shikimic Acids in a PTS<sup>-</sup> Strain of <b><i>Escherichia coli</i></b>

Abstract: The culture of engineered Escherichia coli for shikimic acid (SA) production results in the synthesis of quinic acid (QA) and dehydroshikimic acid (DHS), reducing SA yield and impairing downstream processes. The synthesis of QA by quinate/shikimate dehydrogenase (YdiB, ydiB) has been previously proposed; however, the precise role for this enzyme in the production of QA in engineered strains of E. coli for SA production remains unclear. We report the effect of the inactivation or the overexpression of ydiB in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In addition to the NADP-specific AroE, there is an additional AroE-like shikimate dehydrogenase called YdiB. YdiB plays a role as a dual-specificity quinate/shikimate dehydrogenase that can use either NAD or NADP as cofactors (Michel et al., 2003 ; Garcia et al., 2017 ). The expression of ydiB was increased significantly under carbon-limiting conditions, and it is involved in the catabolism of shikimate (Johansson & Liden, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the NADP-specific AroE, there is an additional AroE-like shikimate dehydrogenase called YdiB. YdiB plays a role as a dual-specificity quinate/shikimate dehydrogenase that can use either NAD or NADP as cofactors (Michel et al., 2003 ; Garcia et al., 2017 ). The expression of ydiB was increased significantly under carbon-limiting conditions, and it is involved in the catabolism of shikimate (Johansson & Liden, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that the molar yield of quinate, a by-product of shikimate biosynthesis, decreased when YdiB was inactivated in the PTS-strain of E. coli , and shikimate production decreased slightly. In contrast, when YdiB was overexpressed, quinate production increased 150% mol/mol compared to shikimate (Garcia et al., 2017 ). In the present study, shikimate was barely produced when the ydiB gene was deleted.…”
Section: Discussionmentioning
confidence: 99%
“…Besides dCpf1-CRISPRi system that controls the PEP consumption, another key node at the branching point is 3-dehydroshikimate (DHS) toward aromatic amino acids (AAAs). DHS can be converted to shikimate by shikimate dehydrogenases (endoded by aroE and ydiB ), which would deplete the intracellular DHS for the heterologous synthesis of muconic acid by DHS dehydratase. , Therefore, aroE and ydiB gene were chosen as CRISPRi targets, and the resulting CRISPRi system was designated as pCDF*-dCpf1-M2 (Figure C). Furthermore, to simultaneously regulate both the central metabolic pathway and aromatic acid biosynthetic pathway, we also combined the above-mentioned two guide RNA arrays, and the resulting CRISPRi system was designated as pCDF*-dCpf1-M3 (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Besides dCpf1-CRISPRi system that controls the PEP consumption, another key node at the branching point is 3dehydroshikimate (DHS) toward aromatic amino acids (AAAs). DHS can be converted to shikimate by shikimate dehydrogenases (endoded by aroE and ydiB), 43 which would deplete the intracellular DHS for the heterologous synthesis of muconic acid by DHS dehydratase. 44,45 Therefore, aroE and ydiB gene were chosen as CRISPRi targets, and the resulting CRISPRi system was designated as pCDF*-dCpf1-M2 (Figure 2C).…”
Section: Development Of Crispri System To Control Thementioning
confidence: 99%
“…Due to this, plasmid-coded feedback resistant ( fbr ) aroF or aroG genes have been expressed. , The intracellular accumulation of shikimic acid can revert the reduction of 3-dehydroshikimic acid into shikimic acid which results in “hydroaromatic equilibration” and formation of byproducts as quinic acid and gallic acids. Inactivation of the shikimic acid transport gene ( shiA ) prevents its cellular reuptake. ,,,, The inactivation of ydiB , a paralog of aroE , also increases the accumulation of shikimic acid by inhibiting the consumption of 3-dehydroquinic acid into quinic acid. , However, the effect observed by activation of ydiB is considerably more pronounced on the accumulation of quinic acid than the effect observed in the accumulation of shikimic acid by inactivation of the same gene . Deletion of genes for shikimate kinase, aroK and aroL , usually requires the fermentation medium to be supplemented with aromatic amino acids to facilitate growth.…”
Section: Synthesis Of Shikimic Acidmentioning
confidence: 99%